Mind Mapping Technique on the Ability to Write Descriptive Text of Vocational High School Students - Kusumadewi, Hermariyanti; Puspitorini, Ferawaty (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2025)
This study aims to analyze the effect of mind mapping technique on the ability to write descriptive text essay of grade X students of SMK Negeri 41 Jakarta. The method used in this research is a quantitative method with true experimental. In this study, the authors gave different types of treatment to two study groups, namely the control group involving 33 students from class X AKL-1 and the experimental group involving 33 students from class X AKL-2. The instrument of this research is essay text descriptive written test. Hypothesis testing in this study used t test. The results of this study indicate that there is significant effect on the application of mind mapping techniques on students' descriptive text essay writing skills, where the ttest is 3.569 and the ttable with n = 64 at a significant level of 5% is 1.6990, in the results of this calculation it can be concluded that 3.569> 1.6990 which means ttest > ttable. Then hypothesis testing was held with the t value obtained from ttest = 3.553 and ttable = 1.6690. Thus, this study successfully tested the truth of the hypothesis that there is a significant effect on the application of mind mapping technique on students' descriptive text writing ability compared to those taught using conventional methods.